Associations between common ECG abnormalities and out-of-hospital cardiac arrest. Issue 1 (21st May 2019) - Søndergaard, Marc Meller; Nielsen, Jonas Bille; Mortensen, Rikke Nørmark; Gislason, Gunnar; Køber, Lars; Lippert, Freddy; Graff, Claus; Haunsø, Stig; Svendsen, Jesper Hastrup; Kragholm, Kristian Hay; Pietersen, Adrian Holger; Lind, Bent Struer; et al.
Abstract : Background: Out-of-hospital cardiac arrest (OHCA) is often the first manifestation of unrecognised cardiac disease. ECG abnormalities encountered in primary care settings may be warning signs of OHCA. Objective: We examined the association between common ECG abnormalities and OHCA in a primary care setting. Methods: We cross-linked individuals who had an ECG recording between 2001 and 2011 in a primary care setting with the Danish Cardiac Arrest Registry and identified OHCAs of presumed cardiac cause. Results: A total of 326 227 individuals were included and 2667 (0, 8%) suffered an OHCA. In Cox regression analyses, adjusted for age and sex, the following ECG findings were strongly associated with OHCA: ST-depression without concomitant atrial fibrillation (HR 2.79; 95% CI 2.45 to 3.18), left bundle branch block (LBBB; HR 3.44; 95% CI 2.85 to 4.14) and non-specific intraventricular block (NSIB; HR 3.15; 95% CI 2.58 to 3.83). Also associated with OHCA were atrial fibrillation (HR 1.89; 95% CI 1.63 to 2.18), Q-wave (HR 1.75; 95% CI 1.57 to 1.95), Cornell and Sokolow-Lyon criteria for left ventricular hypertrophy (HR 1.56; 95% CI 1.33 to 1.82 and HR 1.27; 95% CI 1.12 to 1.45, respectively), ST-elevation (HR 1.40; 95% CI 1.09 to 1.54) and right bundle branch block (HR 1.29; 95% CI 1.09 to 1.54). The association between ST-depression and OHCA diminished with concomitant atrial fibrillation (HR 1.79; 95% CI 1.42 to 2.24, p < 0.01 for interaction). Among patients suffering from OHCA, without a known cardiac disease at the time of the cardiac arrest, 14.2 % had LBBB, NSIB or ST-depression. Conclusions: Several common ECG findings obtained from a primary care setting are associated with OHCA.